AMBULATORY BLOOD PRESSURE MONITORING AFTER PEDIATRIC LIVER TRANSPLANTATION. (June 2018) - Antoniewicz, J.; Czubkowski, P.; Jankowska, I.; Teisseyre, M.; Dadalski, M.; Kaminska, D.; Pawlowska, J.
Abstract : Objective: Due to immunosuppressive treatment, patients after liver transplantation (LTx) are at higher risk of arterial hypertension (HT), which is significant risk factor for cardiovascular disease. Ambulatory blood pressure monitoring (ABPM) is widely used as an extension of casual blood pressure (CBP) measurement. The aim of the study was to investigate the role of ABPM after pediatric LTx. Design and method: CBP was defined as the mean of 2 manual measurements performed on day of ABPM and was classified as normal < 90th percentile (pc), high normal (HN) 90th-95th pc, HT > 95th pc. The result was accepted if at least 70% of total measurement count was approved. Daytime and nighttime mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) were compared to 95th pc values for gender and height. Wake and sleep blood pressure (BP) loads were calculated as the percent of readings at or above the 95th pc. Nocturnal non-dipping (NND) was defined as < 10% difference between the average daytime and nighttime BP. Classification of ABPM was based on current recommendations. Results: CBP, followed by 24h-ABPM were performed in 104 patients (63 females) at the mean age of 13.6 years (10.0–17.8), 10.5 years after LTx (5.1–16.8). Patients presented with stable graft function, and immunosuppression was based on tacrolimus (90%) or sirolimus (10%). Renal function by cystatine-c was > 95th pc in 8% (0.86 ± 0.21). Mean BP was 82.2 ± 6.0 (SBP 109.3 ± 8.8; DBP 67.5 ± 5.9). There were "white coat" HT in 0.9%, HN in 1.9%, masked HT in 4.8%, and severe HT in 2.8% of patients. In 20% of patients there were normal CBP, mean ambulatory BP < 95th pc and BP loads > 25% and 27% had normal CBP, mean ambulatory BP < 95th pc and NND < 10%. Conclusions: Patients after LTx are at higher risk of arterial hypertension. ABPM should be performed routinely during follow-up as a supplement of CBP. Patients with borderline results or unclassified abnormalities should be closely monitored especially before transition to adult care. Significance of nocturnal non-dipping in children after LTx require further studies including assessment of organic cardiovascular damage.